The Concept of Child Education According to Muhammad Quraish Syihab - Azharudin Adnan Firdaus; Rustam Ibrahim (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This article examines the concept of child education according to Muhammad Quraish Shihab, a prominent Muslim scholar whose views are known to be moderate and relevant in the modern era. Shihab emphasizes the importance of education that includes spiritual, moral, and intellectual aspects, with the main foundation of tawhid and noble morals. According to him, the role of parents is very central as the main role model in educating children, which should be done with love and patience. In addition, in the digital era, Shihab encourages the wise use of technology in the education process to equip children to face the challenges of the times without ignoring Islamic values. The implementation of education that he promotes is oriented towards the formation of strong character and religious commitment that can adapt to the times. Shihab's thoughts on children's education are an important reference in answering the challenges of Islamic education in the midst of dynamic social changes.